LISTENING AND UNDERSTANDING THE SPEECH IN LEARNING A FOREIGN LANGUAGE - Daminov Bakhromjon (Zeta Repository, 2023)
There are difficulties inherent in each type of speech activity. The difficulties that occur in listening and understanding are a bit Knowledge of them is one of the decisive conditions for teaching a foreign language. The problems of perception, including understanding speech as perception, have been developed more comprehensively in World Spirituality. This article shows ways to solve these problems.